Integrating the Poor into Universal Health Coverage in Vietnam - Somanathan, Aparnaa; Dao, Huong Lan; Tien, Tran Van (World Bank, Washington DC, 2013)
This case study is aimed at providing a descriptive assessment of the key features of Vietnam's Social Health Insurance (SHI), focusing on the impediments to integrating the poor into universal coverage. The trajectory of SHI in Vietnam is similar to that of many other countries in the East Asia and Pacific region. The poor were covered under a separate Health Care Fund for the Poor to begin with. The 2009 Law on Health Insurance merged all of the different programs into one. Health insurance premiums for the poor were fully subsidized by the government and enrolment became mandatory, resulting in almost complete enrollment of the poor by 2011. Vietnam has combined elements of contributory social health insurance with substantial levels of tax financing to provide coverage for the poor and informal sector. The case study is structured as follows. Section 2 describes the institutional structure and system characteristics of Vietnam's SHI. Section 3 addresses the main topic of the case study - the impediments to integrating the poor. Section 4 concludes by addressing the pending agenda.